Alternative reproductive tactics are associated with sperm performance in invasive round goby from two different salinity environments. Issue 18 (6th September 2020) - Green, Leon; Niemax, Jan; Herrmann, Jens‐Peter; Temming, Axel; Kvarnemo, Charlotta
Abstract: During male–male competition, evolution can favor alternative reproductive tactics. This often results in a dominant morph that holds a resource, such as a nest for egg laying, which competes with a smaller sneaker morph that reproduces by stealing fertilizations. The salinity environment can influence male growth rates, for example, via osmoregulatory costs, which in turn may influence the use of sneaker tactics for small males competing for mating opportunities. Salinity can also affect sperm directly; however, little is known of how salinity influences sneaker tactics through sperm performance. We sampled males of the invasive round goby ( Neogobius melanostomus ) from two environments, a freshwater river and a brackish estuary. This fish has two male morphs: nest‐holding dark males and non‐nest‐holding light males. We examined the role of water salinity of 0, 8, and 16 on sperm performance and found that for estuarine males, a salinity of 0 reduced sperm velocity compared to a salinity of 8 and 16. Riverine males had low velocity in all salinities. Sperm viability also decreased by over 30% in 0 salinity, compared to 8 and 16, for fish from both environments. Gobies produce ejaculate contents in specialized glands that could in theory shield sperm in an adverse environment. However, gland contents did not improve sperm performance in our tests. Body mass and age estimates indicate that riverine males invested more in somatic growth compared to estuarine males. Estuarine light morph males had a high enough gonadosomatic index to indicate sneaker tactics. We propose that when sperm performance is low, such as for the riverine males, sneaker tactics are ineffective and will be selected against or phenotypically suppressed. Instead, we interpret the increased investment in somatic growth found in riverine males as a life‐history decision that is advantageous when defending a nest in the next reproductive season. Abstract : For a male fish too small to defend mating resources such as a female or her eggs, siring offspring can be achieved by sneaking into another male's nest and ejaculating there. In the invasive round goby, this alternative tactic requires sperm to function long enough to fertilize the eggs. This fish has spread into a range of salinities, but for some populations, fresh water decreases sperm velocity and lifespan, and severely limits the use of these alternative reproductive tactics to the point where they may disappear from use.